The Effect of Ensiled Maize Stover Combined with Additives as an Animal Feed - Binti Nur Rohmah; Hartutik Hartutik; Marjuki Marjuki (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The research purpose was to determine the effect of addition starter Pediococcus pentosaceus with different level in the maize stover silage on the in vitro digestibility, fermentation product, and microbial protein synthesis. The treatments consist of T1 = maize stover silage + molasses 10%, T2 = maize stover silage + molasses 10% + P. pentosaceus (1x105 cfu/g), and T3 = maize stover silage + molasses 10% + P. pentosaceus (1x106 cfu/g), fermented for 0 and 21 days. The research method was an experiment by using Randomized Block Design (RBD), with 3 treatments and 4 blocks. The result showed that addition of starter P. pentosaceus in the maize stover silage gave significant effect (P<0.05) on dry matter (T1 (65.67±1.56%), T2 (65.78±0.60%), and T3 (67.54±1.11%)), and organic matter digestibility (T1 (66.93±0.48%), T2 (68.15±1.34%), T3 (68.68±1.04%)) at 21 days incubation. The result of statistical analysis showed that treatment gave significant effect (P<0.05) on gas production at 96 hours of silage with 0 day incubation, T1 (114.74±0.60 ml/500mg DM), T2 (116.12±1.44 ml/500mg DM), T3 (116.97±1.12 ml/500mg DM) and 21 days incubation, T1 (124.27±0.59 ml/500mg DM), T2 (125.27±1.49 ml/500mg DM), and T3 (126.16±1.26 ml/500mg DM). All treatments not gave significant effect (P˃0.05) on degradability, NH3 and microbial protein synthesis on 0 days incubation. However, did it gave significantly effect (P˂0.05) in 21 days incubation silage, dry matter degradability (T1 (66.16±0.42%), T2 (65.70±0.58%), T3 (66.66±0.21%)), organic matter degradability (T1 (65.67±1.56%), T2 (65.78±0.60%), and T3 (67.54±1.11%)), microbial protein synthesis (T1 (37.72±0.13 g/N/kg OM apparently fermented), T2 (37.84±0.64 g/N/kg OM apparently fermented), T3 (38.82±0.56 g/N/kg OM apparently fermented). It can be concluded that addition of starter P. pentosaceus (1x106 cfu/g) on maize stover silage with 21 days incubation can produce silage with good quality on the in vitro digestibility, fermentation product, and microbial protein synthesis.